THE EFFECTIVENESS OF THE VIRTUAL LEARNING MEDIA GRAPH COLORING LABORATORY - Irmayasari Irmayasari; Makrina Tindangen; Evie Palenewen (Program Pascasarjana Universitas Negeri Jakarta, 2021)
The purpose of this study was to determine the effectiveness of virtual laboratory learning media on gram staining material in improving student learning outcomes and retention. The method used in this study is an experiment with a Pretest-Post Nonequivalent Control Group Design . The results showed that the validity of the learning media was 95.6%, the language was 96.4% and the material was 95.5%. The practicality of the media based on teacher questionnaire data is 91.6% and 82.9% of student questionnaires, and the average student learning outcomes increase by 81.9% and the results of student retention power of 87%. Based on the results of the validity, practicality and effectiveness of Biology students and teachers at SMAN 8, SMAN 17 and SMA Wahidiyah Samarinda, it can be concluded that the effectiveness of virtual laboratory media on gram staining material in Biology learning is appropriate to be used as a learning medium.